Binding and legal arbitration in public procurement - Castillo Freyre, Mario (2020)
Application of a mandatory arbitration clause, when differences arise as to the performance or construction of government acquisition and procurement agreements, has represented a momentous change for the public administration, not only in Peru, but in Latin America as a whole. This evidences and emphasizes the efficiency of the arbitrary channel as an alternative conflict solving mean, reducing time, costs and risks in contract relationships between the Government and individuals, thus guaranteeing national and foreign investment. In this order of ideas, although arbitration is applied mandatorily and compulsorily, it does not deny its consensual nature. It also establishes a considerable difference with the General Arbitration Act, which, despite the existence of an arbitration agreement, enables the parties to agree to resort to the Judiciary. So, we have an ipso jure arbitration in public procurement